Profiling for volatile compounds in the Kgalagadi desert truffle - Bogopa, Juda (Rhodes University, Faculty of Science, Department of Chemistry, 2013)
The thesis focuses on 'green' sample preparation techniques that utilise minimal or no organic solvents thereby producing negligible volumes of organic waste, to ensure safety both to user and the environment. Volatile compounds were extracted and pre-concentrated from Kgalagadi desert truffles (kalaharituber) by headspace solid phase microextraction (HSSPME) and supercritical fluid extraction (SFE). PHWE was employed for the extraction of amino acids and fatty acids. Subsequent analysis of volatile compounds was carried out by gas chromatography coupled with mass spectrometry. Four types of HS-SPME fibers (PDMS 100 Î¼m, PDMS 7 Î¼m, Polyacrylate 85 Î¼m, CAR/DVB/PDMS 50/30 Î¼m) were evaluated. A total of 24 volatile compounds with a molecular weight range from 110 to 354, the most prominent peak being 2-t-Butyl-2,3-dimethyl-3-buten-1-ol (Câ‚ â‚€Hâ‚‚â‚€O, MW 156) were detected after sampling with a PDMS 100 Î¼m fiber. Less volatile compounds were detected after SFE with CO2. A total of 16 amino acids were identified while 17 fatty acids (MW from 132.12 to 367.49) were also identified. The characteristic profile of the Kgalagadi desert truffle was found to contain mainly fatty acid methyl esters and unsaturated aliphatic hydrocarbons. The most prominent compound peaks identified were; 2-t-butyl-2,3-dimethyl- 3-buten-1-ol, disulfide, ethyl benzoic acid 2-4-dhydroxy-3,6-dimethyl-methyl ester, 8,11- octadecanoic acid methyl ester, benzoic acid, 2,4-dihydroxy-3,6-dimethyl-methyl ester, isoquinoline, 1 butyl-3,4-dihydro and 3-heptanone, 6 methyl. Optimization results indicated that fresh slices from the heart of truffles were the best to use for HS-SPME-GCMS volatile compound analysis as they showed a higher sensitivity
Keywords: Desert plants -- Botswana -- Kgalagadi District; Supercritical fluid extraction; Gas chromatography; Mass spectrometry; Tuberaceae -- Analysis -- Botswana -- Kgalagadi District; Truffles -- Analysis -- Botswana -- Kgalagadi District